Perceived safety climate in Irish primary care settings—a comparison with Scotland and England - Ciara Curran; Sinéad Lydon; Maureen E. Kelly; Andrew W. Murphy; Caoimhe Madden; Paul O’Connor (European Journal of General Practice, 2018)
Background: Safety climate (SC) measurement is a key component of quality and safety initiatives in primary healthcare. Objectives: To (1) measure perceived SC in Irish primary care; (2) examine whether perceptions of safety varied according to respondent characteristics; and (3) compare responses from our Irish sample to data from England and Scotland. Methods: PC-SafeQuest Survey was administered to all practice staff in Irish general practices between March and May 2016. This survey consists of 30 items across five safety domains (workload, communication, leadership, teamwork, and safety systems). Multiple regression analysis was used to identify predictor variables of perceived safety. The effect size of the difference between the Irish sample’s scores and published English and Scottish data were calculated. Results: A total of 231 questionnaires (38.5%) were returned. Generally, positive perceptions of perceived safety were identified among Irish respondents, but workload had the lowest overall mean score (M = 4.3, SD = 1.2) of the five domains. Comparisons across the Irish, English and Scottish samples identified a medium size effect difference in workload; Scottish respondents perceived workload to have less of a negative impact on safety than Irish or English counterparts (Cohen’s d = 0.602, 0.67 respectively). Analyses indicated that Irish GP principals perceived a more negative impact of workload on safety than administrative staff (β = 0.28, P = 0.03). Conclusion: Irish SC data are largely similar to those of England and Scotland. The perceived potential for workload to negatively impact upon safety emerged within each country. In Ireland, GP principals perceive this as a greater threat than practice administrators do.